Institutional Position of The Tax Court in The Indonesian Judicial System: Between A Court of First Instance and an Appellate Court - Budi Haritjahjono; KMS Herman (Jurnal Sosial Teknologi, 2026)
The Tax Court plays a central role in resolving tax disputes between Taxpayers and tax authorities in Indonesia. Normatively, the Tax Court is established as a special court within the administrative court system. However, the institutional design of the tax judicial system differs from other judicial environments because it does not adopt a hierarchical structure consisting of courts of first instance and appellate courts. This unique structure raises questions regarding the institutional position of the Tax Court within the judicial system under the Supreme Court. This study aims to analyze the institutional position of the Tax Court in the Indonesian judicial system and to examine whether it should be positioned as a court of first instance or as an appellate-level court. This research employs normative legal research using statutory, conceptual, and case approaches. The analysis focuses on legislation governing the judicial system, particularly laws on judicial power, administrative courts, and the Tax Court, as well as relevant Constitutional Court decisions. The findings indicate that, functionally, the Tax Court examines and adjudicates tax disputes at the first and final instance. Nevertheless, substantively, the cases brought before the Tax Court generally arise after administrative objection decisions, which means that the court performs a review function similar to an appellate examination of administrative tax decisions. Therefore, institutionally, the Tax Court is more appropriately understood as a special court that is structurally equivalent to an appellate-level court within the judicial system under the Supreme Court.